1978
DOI: 10.1056/nejm197802022980504
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chlordecone (Kepone) Toxicity with Cholestyramine

Abstract: Industrial workers exposed to the organochlorine pesticide, chlordecone (Kepone), had signs of toxicity in several organs. The extent of toxicity was proportional to the levels of this chemical in the tissues. In 22 patients, chlordecone was eliminated slowly from blood (half time of 165 +/- 27 days--mean +/- S.E.M.) and fat (half time of 125 days, with a range of 97 to 177), chiefly in the stool. Output of chlordecone in bile was 10 to 20 times greater than in stool, suggesting that chlordecone is reabsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
97
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(103 citation statements)
references
References 15 publications
5
97
0
1
Order By: Relevance
“…In humans, chlordecone exposure in occupational circumstances has been associated with a well recognized clinical syndrome involving the nervous system, liver, and testes (Cannon et al, 1978;Cohn et al, 1978;Taylor et al, 1978). Experimental studies in animals confirm all of the toxic effects observed in humans (Faroon et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…In humans, chlordecone exposure in occupational circumstances has been associated with a well recognized clinical syndrome involving the nervous system, liver, and testes (Cannon et al, 1978;Cohn et al, 1978;Taylor et al, 1978). Experimental studies in animals confirm all of the toxic effects observed in humans (Faroon et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Some pesticides and congeners of PCBs can occupy thyroid hormone receptors, and other agents produce symptoms such as infertility in chlordecone (Cohn et al, 1978) and dibromochloropropane (Goldsmith et al, 1984) workers that are plausibly the result of interference with normal endocrine function, even if a hormonal basis is not established. Breast cancer is strongly related to hormone exposure, and has been studied extensively for an environmental hormonal etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most complete data for an environmental agent of this class are the results of studies of 32 workers exposed to high concentrations of the insecticide chlordecone, known more commonly as Kepone. Despite the fact that these workers had high concentrations of chlordecone in their serum, adipose tissue, and liver (20), standard chemical tests were in each case repeatedly negative (21). However, there was liver enlargement and tests for liver Despite the large numbers of people exposed to these chemicals there is surprisingly little information on human liver histopathology.…”
mentioning
confidence: 99%
“…Perhaps the reason that there is so little human liver biopsy material available is that physicians believe liver biopsy is unwarranted in cases of exposure to PCBs or other related chemicals when liver tests are at most only minimally abnormal. This is unfortunate, because liver biopsy performed by an experienced hepatologist carries little risk and in the case of the chlordecone workers provided essential information for diagnosis and management and, ultimately, for designing a rational approach to treatment (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation